Visual Analytics for Open Source Intelligence - Carvalho, R (2015)
Enhanced data visualisation technologies can contribute decisively to companies that rely on making sense of a great amount of information as their primary business objective. Graphical techniques often employed to present processed information and findings to the final customer, such as charts and scatter plots, could be improved and customized to aid analysts during the investigation phase. After examining the internal analysis tasks and data storage strategy from a security consultancy company, this work suggests an approach to enhance knowledge extraction, insight generation and hypothesis testing by applying novel techniques of interactive data visualisation and mining.